1986
DOI: 10.3177/jnsv.32.13
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of 7-dehydrocholesterol, vitamin D3 and 25-hydroxyvitamin D3 in several species of fishes.

Abstract: SummaryA high-performance liquid chromatographic (HPLC) meth od for simultaneous determination of 7-dehydrocholesterol (7-DHC), vitamin D3 and 25-hydroxyvitamin D3 (25-OH-D3) in tissues of fishes was established, and using this method the tissue distribution of the sterols in lamprey (Entosphenus japonicus), great blue shark (Prionace glauca), skipjack (Katsuwonus pelamis) and albacore (Thunnus alalunga) was in vestigated. The results are summarized in the following: 1) Although the alimentary canal, gall blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…An internal analytical report from the MAFF in the UK found 25OHD 3 contents of 0.11 Ìg/ 100 g in the flesh of raw salmon and 0.22 Ìg/100 g in raw trout, which are much lower than the measured vitamin D 3 concentrations in the same samples of 5.4 and 8.1 Ìg/ 100 g, respectively [32]. While liver (and oils) in some fish species contains very large amounts of vitamin D 3 , only insignificant amounts of 25OHD 3 are usually present in the liver and other viscera [33].…”
Section: Fish and Fish Productsmentioning
confidence: 90%
“…An internal analytical report from the MAFF in the UK found 25OHD 3 contents of 0.11 Ìg/ 100 g in the flesh of raw salmon and 0.22 Ìg/100 g in raw trout, which are much lower than the measured vitamin D 3 concentrations in the same samples of 5.4 and 8.1 Ìg/ 100 g, respectively [32]. While liver (and oils) in some fish species contains very large amounts of vitamin D 3 , only insignificant amounts of 25OHD 3 are usually present in the liver and other viscera [33].…”
Section: Fish and Fish Productsmentioning
confidence: 90%
“…Several investigators have studied the presence of vitamin D metabolites in various teleosts (1)(2)(3)(4)(5)(6) and the changes in the blood calcium and phosphate contents of fish after administration of vitamin D and/or its metabolites (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies reported a lack of any relation between provitamin D3 and vitamin D3 contents in several fish (10,11,14) and also that the levels of these two compounds in the skin of fish were lower than those of rats (15), suggesting that the photochemical synthesis of vitamin D3 might not be significant in fish. It has been * To whom correspondence should be addressed .…”
Section: Discussionmentioning
confidence: 98%
“…On exposure to sunlight, the 5,7-diene of 7-DHC (steroid) absorbs ultraviolet (UV) energy (spectral range 290-315nm) that causes the cleavage of C9-C10 bond in the "B ring" to form vitamin D3 (secosteroid) (5-7) . Thus, "sunlight" is the chief energy source for breaking the B-ring of steroid in land animals.Interestingly, certain fish liver oils are rich sources of vitamin D [25,000 250,000IU/g oil (8-11)] when compared to mammals [<1IU/g oil (12)], inspite of the non-availability of enough UV light in their natural habitats (13).Earlier studies reported a lack of any relation between provitamin D3 and vitamin D3 contents in several fish (10,11,14) and also that the levels of these two compounds in the skin of fish were lower than those of rats (15), suggesting that the photochemical synthesis of vitamin D3 might not be significant in fish. It has been * To whom correspondence should be addressed .…”
mentioning
confidence: 99%